HUBUNGAN INDEKS MASSA TUBUH (IMT) DENGAN BENTUK ARKUS KAKI PADA ANAK USIA 7 – 12 TAHUN DI SDN 03 TOHUDAN KARANGANYAR - Muhammad Fathi; Sisybania; Anggita Putri Nugraheni (Jurnal Medicare, 2026)
Abnormal foot arch shape can cause balance disorders, pain, and increase the risk of injury. One factor influencing this condition is Body Mass Index (BMI). Children with high BMI, such as overweight and obesity, tend to have flat foot arches (pes planus) due to greater body weight. This study aims to determine the relationship between foot arch shape and BMI in elementary school children. This study at SDN 03 Tohudan Karanganyar using an analytical observational method with a cross-sectional approach. The sample consisted of 92 students selected through total sampling. BMI was measured using body weight and height, while foot arch shape was assessed using the Clarke Angle method. Data analysis included normality testing and hypothesis testing using the Spearman Rank test.The results showed a significant relationship between BMI and foot arch shape, with a p-value of 0.013 (p < 0.05) and a correlation coefficient of -0.258. This negative correlation indicates that as BMI increases, foot arch shape decreases. However, the correlation strength was weak. In conclusion, there is a significant negative relationship between BMI and foot arch shape in children aged 7–12 years. Higher BMI is associated with lower foot arch shape, which may increase the risk of musculoskeletal disorders.